Supported employment programme for persons with severe mental disorders in India: A feasibility study. (September 2020) - Jagannathan, Aarti; Harish, Nikitha; Venkatalakshmi, C; Kumar, C Naveen; Thirthallli, Jagadisha; Kumar, Devvarta; Bhola, Poornima; Prasad, M Krishna; Thanapal, Sivakumar; Hareesh, A; Jayarajan, Deepak; Govindan, Radhakrishnan; et al.
Background: A number of persons with severe mental illnesses are unable to prepare for, find or keep a job due to factors linked to their illness as well as psychosocial issues. Aim: To test the feasibility of a supported employment programme to help persons with severe mental disorders obtain and sustain employment. Methods: A supported employment programme was developed for persons with severe mental disorders with components of (a) assessment of vocational potential, (b) vocational counselling, (c) networking and liaison with prospective employers, (d) job-related training and placement and (e) continued support for 6 months. Job placement status, social occupational functioning and disability (quantitative data) and benefits of enrolling in the employment programme (qualitative data) were assessed. Results: A total of 40 employers were liaised with for providing job placement and reasonable accommodation. Out of 63 participants recruited into the study, 32 (50.8%) participants were placed in competitive jobs, placement was actively attempted for 17 (27.0%) participants, 7 (11.1%) were referred for skill training and 7 (11.1%) dropped out from the study. The disability score significantly reduced and socio-occupational functioning significantly improved in those who were placed over a period of 6 months. Conclusion: The supported employment programme was found to be feasible as it showed good placement rates and improvement in socio-occupational functioning and disability scores